An insight into the genetic variation of Schistosoma japonicum in mainland China using DNA microsatellite markers. - Shrivastava, J; Qian, B; Mcvean, G; Webster, J (2005)
This study presents the first microsatellite investigation into the level of genetic variation among Schistosoma japonicum from different geographical origins. S. japonicum isolates were obtained from seven endemic provinces across mainland China: Zhejiang (Jiashan County), Anhui (Guichi County), Jiangxi (Yongxiu County), Hubei (Wuhan County), Hunan (Yueyang area), Sichuan 1 (Maoshan County), Sichuan 2 (Tianquan County), Yunnan (Dali County), and also one province in the Philippines (Sorsogon). DNA from 20 individuals from each origin were screened against 11 recently isolated and characterized S. japonicum microsatellites, and a set of nine loci were selected based on their polymorphic information content. High levels of polymorphism were obtained between and within population samples, with Chinese and Philippine strains appearing to follow different lineages, and with distinct branching between provinces. Moreover, across mainland China, genotype clustering appeared to be related to habitat type and/or intermediate host morph. These results highlight the suitability of microsatellites for population genetic studies of S. japonicum and suggest that there may be different strains of S. japonicum circulating in mainland China.